ANALYSI S ON SECONDARY I NFECTI ON- TRI GGERI NG MICROORGANISMS IN HIV/AIDS PATIENTS AS A MODEL FOR POLICY CONTROL - Rahayu, Retno Pudji; Nasronudin, Nasronudin; Indrawati, Retno; Widiyanti, Prihartini; Lukito, Bimo Dwi; Ferdiansyah, Ferdiansyah; Khairunisa, Siti Qomariyah; Mutamsari, Adiana; Kotaki, Tomohiro (Institute of Topical Disease Universitas Airlangga, 2015)
HIV infection is associated with immune-compromised and rising in opportunistic infection (secondary infection). Therefore, the number of mortality caused by HIV/AIDS is increasing. The use of ARV and development of HIV/AIDS management are expected to suppress the progress of HIV infection into AIDS and, therefore, the mortality can be diminished, while in fact most of the patients eventually suffer from AIDS due to secondary infection that commonly causes death. There should be a management by analysing microorganisms that trigger secondary infection. The method of this study was observational descriptive with cross sectional design. HIV infected blood samples were using ELISA Antibody (IgG and IgM) and Polymerase Chain Reaction (PCR) on laboratory test. The result showed correlation between HIV/AIDS severity and the amount and types of secondary infection. The most common secondary infections were toxoplasm (96.77%), hepatitis C (22.58%), tuberculosis (19.35%), and hepatitis B (3.22%). Other less frequent secondary infections, which were quite difficult to diagnose and not commonly found in Indonesia, were West Nile Virus (25.81%), Japanese Encephalitis Virus (3.22%), and Enterovirus (3.22%). Due to MDGs (Millenium Development Goals) target and the results above, researchers are highly demanded to contribute in decreasing mortality related to AIDS through early detection of secondary infection,including type of infection which have not been commonly found in Indonesia, such as West Nile Virus and Nipah Virus. The discovery of secondary infection in this study was not enough to suppress the occurrence of infection in HIV/AIDS patients. Antimicrobes and good nutrition are required. Moreover, there should be either a primary or secondary prophylaxis to prevent secondary infection that raises the number of mortality and morbidity of HIV/AIDS patients. The result of this study was to meet the target of MDGs by establishing new policies in handling HIV/AIDS infections and have potential as model for policy control in HIV/AIDS.